2007
DOI: 10.1210/en.2007-1321
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 5-HT2C Receptor Agonist Promotes Hypophagia via Downstream Activation of Melanocortin 4 Receptors

Abstract: The neurotransmitter serotonin (5-hydroxytryptamine) is a well-established modulator of energy balance. Both pharmacological and genetic evidence implicate the serotonin 2C receptor (5-HT(2C)R) as a critical receptor mediator of serotonin's effects on ingestive behavior. Here we characterized the effect of the novel and selective 5-HT(2C)R agonist BVT.X on energy balance in obese and lean mice and report that BVT.X significantly reduces acute food intake without altering locomotor activity or oxygen consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
185
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(198 citation statements)
references
References 28 publications
9
185
0
4
Order By: Relevance
“…This is surprising because 2CR are expressed in both the Arc and PVN (27,28), because pharmacological data implicate both the PVN and Arc in the serotonergic control of eating (50,59), because 2CR-serotonergic inputs to the Arc-PVN melanocortinergic neurons appear to be part of the physiological control of eating in mice (3,36,38), and because both the PVN and the Arc have been implicated in the satiating action of CCK (13,17,35,37,38,42). Furthermore, the absence of CCK-induced c-Fos activation in the NTS of 2CR KO mice suggests that NTS-tohypothalamus signaling would be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising because 2CR are expressed in both the Arc and PVN (27,28), because pharmacological data implicate both the PVN and Arc in the serotonergic control of eating (50,59), because 2CR-serotonergic inputs to the Arc-PVN melanocortinergic neurons appear to be part of the physiological control of eating in mice (3,36,38), and because both the PVN and the Arc have been implicated in the satiating action of CCK (13,17,35,37,38,42). Furthermore, the absence of CCK-induced c-Fos activation in the NTS of 2CR KO mice suggests that NTS-tohypothalamus signaling would be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…receptor agonists to exert effects on food intake [166]. However, a more recent study, likewise using MC4 knockout mice, but also MC3 knockout mice, found rather evidence that MC3 receptors are the more likely candidate [167].…”
Section: Brain Mechanisms Of Serotonergic Satietymentioning
confidence: 99%
“…An improved understanding of the role of Ahi1 in the metabolic side effects of antipsychotic drugs may help provide the potential target to alleviate these adverse effects. Both pharmacological and genetic evidence implicates 5-HT 2C R as a critical receptor mediator of the effect of serotonin on feeding behavior (12,52,63,64). Recent animal studies using knock-out mice have shown the 5-HT 2C R gene to be involved in the control of appetite and feeding behavior.…”
Section: Discussionmentioning
confidence: 99%